(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
The article provides a brief analysis of characters in Shukhrat’s novel “Gold is stainless”. In the work, we can meet not only intellectuals during the war years, but also cases of repression of ordinary people, as well as heroes who are loyal to the motherland and family-loving, as well as traitors to the country. The attitude towards women, the hardships they went through, the loss of mothers from their children, young brides from their husbands, the patience of Uzbek women is vividly reflected through artistic images.